A transferable method for estimating the economic impacts of track interventions: Application to ground-borne noise reduction measures for whole sections of route. (July 2021) - Young, Marcus; Rempelos, Georgios; Ntotsios, Evangelos; Blainey, Simon; Thompson, David; Preston, John
The environmental impacts of noise and vibration are becoming increasingly important in the assessment of new and upgraded railway routes. Vibration from railways propagates through the ground to nearby buildings where it may cause annoyance as feelable vibration or as re-radiated noise. To tackle the adverse effects of ground-borne noise a range of possible interventions are available, including softer rail pads, under-sleeper pads and under-ballast mats. The installation costs of such interventions are generally higher for the higher-performing track types. Additionally, there are potential effects on track maintenance costs which may be positive or negative, for example by reducing sleeper damage or increasing the need for ballast tamping. This study presents a socio-economic analysis of the effects of several interventions to reduce ground-borne noise. By selecting a whole route, the installation and whole-life costs are assessed using Network Rail's Vehicle-Track Interaction Strategic Model (VTISM) and these are offset against benefits in terms of reduced social costs. Ground-borne noise is predicted at various distances from the alignment using the Modelling of Train Induced Vibration (MOTIV) model and the effect of track interventions is determined as insertion loss spectra. The re-radiated noise within a typical domestic building is then estimated using generic building transfer functions. Geographic Information System tools are used to estimate the population affected by ground-borne noise and their expected level of exposure. The methodology is illustrated using a case study route between Brighton and Portsmouth in the South of England.